ANALISIS DEBRIS AKIBAT TSUNAMI DAN PENGARUHNYA PADA GAYA YANG DITERIMA BANGUNAN - , Maulina Indriyani, Prof. Ir. Radianta Triatmadja, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Based on its geographical location, Indonesia is located at the confluence of three major tectonic plates. Because of that condition, Indonesia is prone to tectonic earthquake and tsunami. One of the worst tsunami in the world was occurred in Aceh on December 26th 2004 that caused 226.889 casualties and U.S. $ 10 billion damages, equivalent to 100 trillion rupiahs (NOAA, 2013). The large damages in the tsunami is caused by the large force when it hits a building. That damages may be worse when tsunami carries debris. This research was focused to learn about the influence of debris to the surge velocity and the force at building. This research was conducted in the Laboratory of Hydrology and Hydraulics, Engineering Science Center, Universitas Gadjah Mada. Tsunami was generated using a dam break system. This research was carried out under conditions of clear water and tsunami with debris. The total force on the building was measured using a load cell. The height and the velocity of surge in clear water condition were measured using the wave probe, while in tsunami with debris were measured using a camera. Debris was placed in front of the building with 50 cm, 100 cm, and 150 cm distances from the center of debris to the front of building. Water depth at the upstream of dam break was varied as deep as 20 cm, 25 cm, 30 cm, 35 cm, and 40 cm. The results showed that debris scattered along the Â±10 times of the surges height with a diameter 0.44 times of the surges height makes the surges velocity reduce to 15% of the initial surges velocity. As for the force that occur in buildings from the tsunami that carries debris increased when it compared to the clear water condition. In condition with debris scattered in front of the building, the force was ranging from 2.2 to 4.8 times of the force in clear water condition. Theoritically, the debris velocity can be written as the function of the surge velocity and the initial debris velocity. While the total force of tsunami with debris can be written as the surge force added by the impact force. Hopefully, this research can be used as the reference of the constructions planning with consideration of the debris impact force.